Two mole crab species of Emerita Scopoli, 1777 (Decapoda: Anomura: Hippidae) from Java Island, Indonesia, with description of a new species - Farajallah, Achmad; Hanim, Nisfa; Putri, Vinna Windy; Wardiatno, Yusli (Zootaxa, 2025)
Previously, only one species of the genus Emerita Scopoli, 1777, E. emeritus (Linnaeus, 1767), was documented in Indonesia. It was reported along the western coast of Sumatra Island and the southern and northern coasts of Java Island. Here, we describe a new species, Emerita pangandaran sp. nov., that distinguishes itself from E. emeritus by having crenulate, as opposed to smooth, anterior margins of the carapace. The new species was found only in Pangandaran Beach and Cilacap in southern Java. Genetic distances and phylogenetic analysis based on partial sequences of the COI gene further distinguish the new species from E. emeritus.